CodY Regulates the Activity of the Virulence Quorum Sensor PlcR by Controlling the Import of the Signaling Peptide PapR in Bacillus thuringiensis - Slamti, Leyla; Lemy, Christelle; Henry, Céline; Guillot, Alain; Huillet, Eugénie; Lereclus, Didier (Frontiers in Microbiology, 2016)
In Gram-positive bacteria, cell-cell communication mainly relies on cytoplasmic sensors of the RNPP family. Activity of these regulators depends on their binding to secreted signaling peptides that are imported into the cell. These quorum sensing regulators control important biological functions in bacteria of the Bacillus cereus group, such as virulence and necrotrophism. The RNPP quorum sensor PlcR, in complex with its cognate signaling peptide PapR, is the main regulator of virulence in B. cereus and Bacillus thuringiensis (Bt). Recent reports have shown that the global stationary phase regulator CodY, involved in adaptation to nutritional limitation, is required for the expression of virulence genes belonging to the PlcR regulon. However, the mechanism underlying this regulation was not described. Using genetics and proteomics approaches, we showed that CodY regulates the expression of the virulence genes through the import of PapR. We report that CodY positively controls the production of the proteins that compose the oligopeptide permease OppABCDF, and of several other Opp-like proteins. It was previously shown that the pore components of this oligopeptide permease, OppBCDF, were required for the import of PapR. However, the role of OppA, the substrate-binding protein (SBP), was not investigated. Here, we demonstrated that OppA is not the only SBP involved in the recognition of PapR, and that several other OppA-like proteins can allow the import of this peptide. Altogether, these data complete our model of quorum sensing during the lifecycle of Bt and indicate that RNPPs integrate environmental conditions, as well as cell density, to coordinate the behavior of the bacteria throughout growth.